A simple ecuation

Algebra Level 3

Find the least root for the ecuation x 3 10 x 2 + 9 x 1 = 0 x^{-3} - 10x^{-2} + 9x^{-1} = 0

0 1 9 1 9 \frac{1}{9}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Andrea Palma
May 15, 2015

Call t = x 1 t = x^{-1} .

The equation became

t 3 10 t 2 + 9 t = 0 t^3 -10t^2 +9t = 0

that is

t ( t 1 ) ( t 9 ) = 0 t(t-1)(t-9)=0

whose roots are 0 , 1 0, 1 and 9 9 .

Turning back in x x we find x = 1 x=1 and x = 1 9 x = \dfrac{1}{9} (the t = 0 t=0 doesn't lead to an acceptable x x solution) the least of which is 1 9 \dfrac{1}{9} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...